A novel LDEM formulation with crack frictional sliding to estimate fracture and flexural behaviour of the shot-earth 772. (1st February 2023) - Colpo, Angélica; Vantadori, Sabrina; Friedrich, Leandro; Zanichelli, Andrea; Ronchei, Camilla; Scorza, Daniela; Iturrioz, Ignacio
Highlights: Shot-earth 772 fracture and flexural behaviour is numerically investigated by LDEM. A novel constitutive law for the discrete elements is proposed. Damage due to material degradation is taken into account in the constitutive law. Frictional sliding along rough crack surfaces is considered in the constitutive law. Satisfactory agreement between numerical and experimental results is observed. Abstract: In the present paper, both the fracture and flexural behaviour of an innovative material, named shot-earth 772, is carried-out by employing numerical simulations performed by using the Lattice Discrete Element (LDE) method. More precisely, a novel constitutive law for the discrete elements is proposed, which takes into account the damage due to both material degradation and frictional sliding along rough crack surfaces and the residual strain effect. The comparison between the numerical results and the experimental ones highlights that the LDE model proposed is able to numerically simulate both the fracture and the mechanical behaviour of the shot-earth 772 up to failure, with a quite satisfactory accuracy.